Waste Management Strategies, Facility Enhancement, and Accident and Disaster Mitigation at Angke Kapuk Nature Tourism Park in Promoting the Achievement of the Sustainable Development Goals (SDGs) - Garry Jordanius; Ika Suryono Djunaid (Darul Yasin Al Sys, 2026)
Mangrove ecotourism destinations require integrated management strategies to address environmental degradation, deteriorating facilities, visitor safety, and climate-related coastal risks while contributing to the Sustainable Development Goals (SDGs). Taman Wisata Alam (TWA) Angke Kapuk, a 99.82-hectare mangrove ecotourism area in North Jakarta, faces persistent challenges involving marine debris, facility deterioration, limited risk-mitigation systems, and a decline in domestic tourist visits from 88,516 in 2022 to 43,734 in 2025. This study aims to analyze waste management, tourism facility improvement, and accident and coastal environmental risk-mitigation strategies at TWA Angke Kapuk in support of the SDGs. Grounded in Sustainable Tourism Development, Destination Management, and Ecotourism theories, the study employed a descriptive qualitative case study design. Data were collected through semi-structured interviews with government representatives, site managers, tour guides, and visitors, supplemented by field observations and documentation. Internal and external strategic factors were examined using SWOT analysis supported by IFAS and EFAS matrices. The findings indicate that waste management incorporates segregated bins, internal waste sorting, collaboration with a waste bank, and debris nets, but remains constrained by limited personnel, low visitor awareness, inactive composting, and uncontrolled marine debris. Although tourism facilities are relatively complete, boardwalks, gazebos, bird observation towers, and toilets have deteriorated, while accessibility for persons with disabilities remains inadequate. Accident mitigation is still basic, whereas tidal flooding, extreme weather, and humidity-related infrastructure damage require adaptive coastal-risk management rather than exclusively disaster-oriented responses. IFAS and EFAS scores of 2.95 and 2.98, respectively, indicate a moderately strong internal position and a reasonable capacity to exploit external opportunities despite continuing threats. The study concludes that sustainable management at TWA Angke Kapuk is most directly associated with SDGs 11, 12, 13, 15, and 17, while SDG 14 constitutes a supporting linkage. These findings contribute an integrated strategic framework for mangrove ecotourism management and imply the need to strengthen visitor education, prioritize facility maintenance, implement adaptive coastal-risk mitigation, and expand multi-stakeholder collaboration.